2018
DOI: 10.20452/pamw.4210
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic utility of the N terminal prohormone of brain natriuretic peptide and the modified Model for End Stage Liver Disease in patients with end stage heart failure

Abstract: INTRODUCTION    The N terminal prohormone of brain natriuretic peptide (NT proBNP) is secreted by cardiomyocytes in response to increased wall stress resulting from pressure and volume overload. The modified Model for End Stage Liver Disease (modMELD) scale reflects the systemic effect of heart failure (HF), which includes end-organ congestion and subsequent hepatic and renal dysfunction. OBJECTIVES    The aim of this study was to assess the prognostic accuracy of NT proBNP and the modMELD score, as well as to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 16 publications
1
10
0
Order By: Relevance
“…However, NT-proBNP slightly improved the prognostic power of the HFSS score to predict one-year mortality in the analyzed group of patients. Natriuretic peptides play an important regulatory role in responding to the increase in ventricular volume by opposing vasoconstriction, sodium retention and antidiuretic effects of the activated renin-angiotensin-aldosterone system [ 12 , 21 ]. In clinical practise, NT-proBNP is commonly used to aid the diagnosis of HF, assess the effect of therapy and predict the outcomes at different stages of HF [ 1 , 22 , 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, NT-proBNP slightly improved the prognostic power of the HFSS score to predict one-year mortality in the analyzed group of patients. Natriuretic peptides play an important regulatory role in responding to the increase in ventricular volume by opposing vasoconstriction, sodium retention and antidiuretic effects of the activated renin-angiotensin-aldosterone system [ 12 , 21 ]. In clinical practise, NT-proBNP is commonly used to aid the diagnosis of HF, assess the effect of therapy and predict the outcomes at different stages of HF [ 1 , 22 , 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…These conditions may limit the value of NT-proBNP to predict survival in patients with end-stage HF. Furthermore, as our previous study has shown [ 12 ], the relatively limited prognostic power of NT-proBNP may result from the fact that our population included a selected optimally treated group of stable patients with end-stage HF. Optimal neurohormonal suppression with maximal HF therapy may also limit the prognostic performance of this marker and contribute to the lack of significant improvement of prognostic strength in the combination of NT-proBNP with HFSS and MAGGIC, as compared to adding apelin to these scales.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…failure In everyday clinical practice, the assessment of HF exacerbation is based on clinical examination, chest radiography, N -terminal fragment of the prohormone brain natriuretic peptide (NT -proBNP) levels, and echocardiography. 30,31 Physical examination is still the initial diagnostic modality. However, it does not yield reliable results in asymptomatic patients and does not allow for a precise assessment of the degree of HF exacerbation.…”
Section: Clinical Usefulness Of Lung Ultrasound In Heartmentioning
confidence: 99%
“…Developing a CF -LVAD-dedicated risk scale including hemodynamic, clinical, and biochemical factors-predictors of survival, could also be helpful in determining an optimal time frame for OHT during LVAD support, as it has been explored in some studies of non -LVAD patients with endstage HF who awaited OHT. 22,23 Study limitations Our study had some limitations owing to its retrospective design. In several patients, data were missing, including information on RHC before implantation.…”
mentioning
confidence: 97%